ANALISIS TINGKAT PEMAHAMAN MAHASISWA TERHADAP PENGGUNAAN VIRTUAL LAB DALAM PRAKTIKUM - Kurniawati, Atik; Eka Sudiwati, Ni Luh Putu (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
The advancement of digital technology has significantly influenced innovation in health vocational education. One such innovation is the use of virtual laboratories as simulation-based practicum media. This study aims to analyze students’ understanding levels regarding the use of virtual labs in Blood Group Serology Practicum at the Diploma III Blood Bank Technology Study Program, Poltekkes Kemenkes Malang. This research employed a quantitative descriptive method using a survey approach. The respondents were 68 students who had participated in the virtual lab practicum. Data were collected using a 5-point Likert-scale questionnaire covering conceptual understanding, user perception, and technical constraints. The findings revealed that students’ understanding levels of virtual lab usage were in the good to very good category, with an overall mean score of 4.61 ± 0.71. The conceptual understanding aspect achieved the highest mean score (4.69), indicating students’ strong comprehension of antigen–antibody reactions and agglutination interpretation. Meanwhile, the technical constraint aspect showed the lowest mean score (2.63), suggesting minimal technical issues. These results indicate that virtual laboratories are effective in enhancing conceptual understanding and serve as an efficient, safe, and competence-based alternative learning media in health vocational education.